Pour une communication organisationnelle affective : une perspective préindividuelle de l’action et de la constitution des organisations - Nicolas Bencherki (Communiquer, 2015)
This text suggests that adopting a particular version of affect theories, which are still lacking recognition in organizational communication, allows overcoming the dilemma of organizational action – is it the individual or the organization that’s acting – not by resolving it, but by allowing a totally different understanding of the constitution and action of collectives. By starting from the preindividual – a notion coined by French philosopher Gilbert Simondon – rather than from the individual, it is possible to study the concrete ways by which entities capture each other’s action to engage in an individuation process. Communication is then viewed as the propagation of action ; signification for its part depends on the action’s participation to a particular individuation process. The preindividual perspective will be illustrated through the analysis of excerpts from the documentary Nomad’s Land, directed by Claire Corrriveau (2007), where she recounts the intricate relationship between military wives and the Canadian army.